Bone Autograft Coupled with Locking Plates Repairs Symptomatic Rib Fracture Nonunions. Issue 6 (June 2018) - Hernandez, Matthew C.; Reisenauer, Janani S.; Aho, Johnathon M.; Zeb, Muhammad; Thiels, Cornelius A.; Cross, William W.; Schiller, Henry J.; Kim, Brian D.
Symptomatic rib nonunions are a rare complication after rib fractures. Methods used to address these nonunions range from pain management, rib resection, and rib fixation with plates and occasional autologous bone grafting. Given potential complications associated with rib resections such as pulmonary hernia, we hypothesized that plate fixation and autologous bone grafting would yield satisfactory long-term outcomes and a high union rate. Patients (aged ≥18 years) at a single institution with a symptomatic rib nonunion who underwent surgical rib stabilization of the nonunion coupled with bone autograft were evaluated (2010–2014). Pertinent clinical, operative, radiologic, and follow-up data were abstracted. Univariate analyses to assess the relationship of clinical outcomes were performed. Six patients underwent nonunion repair with autograft and plating. The mean time from injury to surgical repair of nonunion was 15 (66.1) months. A median of 3 [1–3] ribs were repaired with surgery. Postoperative radiographic union was demonstrated on cross-sectional imaging at three months in four patients (57%) and in all patients at five months postoperatively. No patients developed postoperative pulmonary hernia during follow-up. All patients had a significant reduction in median patient-reported pain at follow-up. Surgical rib fixation and bone autograft can provide acceptable outcomes for patients with rib fracture nonunion. This method provides pain relief and promotes healing of the nonunion gap without pulmonary hernia development. Operative fixation and bone autograft should be considered as a viable technical alternative to resection alone for rib nonunion.